Effectiveness of Strategic Performance and the Impact of Balanced Scorecard on DKI Jakarta Government Achievements - Oktari, Vivi; Nur, Sofyan Ashari (Politeknik Raflesia Press, 2024)
Anggitaningsih, R., Irawan, B., Prihatini, D., & Barokah, I. (2023). The Effect of Balanced Scorecard Understanding on Employee Performance with Career System and Compensation System as Moderating Variable. Calitatea, 24(192), 306–316. Anggitaningsih, R., Irawan, B., Prihatini, D., & Barokah, I. (2023). Pengaruh Pemahaman Balanced Scorecard terhadap Kinerja Karyawan dengan Sistem Karir dan Sistem Kompensasi sebagai Variabel Moderasi. Calitatea, 24(192), 306–316. Bouckaert, G., & Van Dooren, W. (2003). Performance measurement and management in public sector organizations. Bshayreh, M. M., Qawqzeh, H. K., Al-Momany, I. A. A., Saleh, M. M. A., & Al Qallap, K. D. H. (2024). The Influence of Balanced Scorecard Perspectives on the Firms’ Performance: Evidence from the Banks in the Developing Market. Cignitas, C. P., Torrents Arévalo, J. A., & Vilajosana Crusells, J. (2021). Balanced scorecard, the key to employee well-being the impact of balanced scorecard on employee well-being: The case of state of Michigan-USA. International Journal of Business & Management, 9(12), 175–197. CIGNITAS, C. P., Arevalo, J. A. T., & Crusells, J. V. (2022). The effect of strategy performance management methods on employee well-being: A case study analyzing the effects of balanced scorecard. Dabor, A. O., Dabor, E. L., Eguasa, B. E., Atarere, L. O. I., & Abusomwa, R. E. (2023). Balance Scorecard and Performance of Money Deposit Bank in Nigeria. Nigerian Academy of Management Journal, 18(1), 12–29. Davis, S., & Albright, T. (2004). An investigation of the effect of balanced scorecard implementation on financial performance. Management Accounting Research, 15(2), 135–153. Dhariwal, P., & Nichol, A. (2021). Diffusion models beat GANs on image synthesis. Advances in Neural Information Processing Systems, 34, 8780–8794. Duwe, A. (2024). Effectiveness of Balanced Scorecard Performance Management System on Provision of Quality Services (Doctoral dissertation, The Open University of Tanzania). Gazi, F., Atan, T., & Kılıç, M. (2022). The assessment of internal indicators on the balanced scorecard measures of sustainability. Sustainability, 14(14), 8595. He, K., Chen, X., Xie, S., Li, Y., Dollár, P., & Girshick, R. (2022). Masked autoencoders are scalable vision learners. In Proceedings of the IEEE/CVF Conference on Computer Vision and Pattern Recognition (pp. 16000–16009). Istiarsono, Z. (2022). Penerapan balanced scorecard dalam bidang pendidikan: Kajian teoretik. Intelegensi: Jurnal Pendidikan dan Pembelajaran, 7(1), 1–9. Jassem, S., Zakaria, Z., & Che Azmi, A. (2022). Arsitektur balanced scorecard keberlanjutan dan hasil kinerja lingkungan: Tinjauan sistematis. Jurnal Internasional Produktivitas dan Manajemen Kinerja, 71(5), 1728–1760. Khaleeli, M., Faisal, R., & Anwar, S. (2021). The effect of green marketing, green supply chain and green human resources on business performance: Balanced scorecard approach. Uncertain Supply Chain Management, 9(1), 133–138. Liu, Z. (2024). Implementation of the balanced scorecard in large firms: A systematic review. Asian Journal of Accounting and Finance, 6(2), 1–11. Miliki, A. (2024). Efektivitas Sistem Manajemen Kinerja Balanced Scorecard pada Penyediaan Pelayanan Berkualitas (Disertasi Doktoral, The Open University of Tanzania). Mushtaha, A., Aljifri, K., & Zoubeidi, T. (2024). Critical success factors of effective implementation of balanced scorecard and organisational performance: Case of UAE private hospitals. Journal for International Business and Entrepreneurship Development, 16(3), 425–446. Nour, A. I., Alamleh, L. W., Al-Atoot, S. M., & Almomani, K. M. (2022). Pengaruh penerapan balanced scorecard terhadap kualitas laba di antara bank-bank yang terdaftar di Palestine Exchange. Jurnal Humaniora dan Ilmu Sosial Universitas Cihan-Erbil, 6(1), 101–112. Rafiq, M., Maqbool, S., Martins, J. M., Mata, M. N., Dantas, R. M., Naz, S., & Correia, A. B. (2021). A study on balanced scorecard and its impact on sustainable development of renewable energy organizations; A mediating role of political and regulatory institutions. Risks, 9(6), 110. Sharaf-Addin, H. H., & Fazel, H. (2021). Balanced scorecard development as a performance management system in Saudi Public Universities: A case study approach. Asia-Pacific Journal of Management Research and Innovation, 17(1–2), 57–70. Torrents Arévalo, J. A., Vilajosana Crusells, J., & Cignitas, C. P. (2022). Literature review on the effect of balanced scorecard on employee wellbeing. International Journal of Business and Management, 17(3), 103–120. Van Thuong, C., & Singh, H. (2023). Dampak balanced scorecard terhadap kinerja perusahaan di Kota Ho Chi Minh, Vietnam. Jurnal Internasional Kepemimpinan Organisasi, 12(2). Waworuntu, E. C., Kainde, S. J., & Mandagi, D. W. (2022). Work-life balance, job satisfaction, and performance among millennial and Gen Z employees: A systematic review. Society, 10(2), 384–398.